2016
DOI: 10.1107/s1600576716005574
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving the spatially resolved preferred orientation of embedded anisotropic particles by small-angle X-ray scattering tomography

Abstract: Experimental nondestructive methods for probing the spatially varying arrangement and orientation of ultrastructures in hierarchical materials are in high demand. While conventional computed tomography (CT) is the method of choice for nondestructively imaging the interior of objects in three dimensions, it retrieves only scalar density fields. In addition to the traditional absorption contrast, other contrast mechanisms for image formation based on scattering and refraction are increasingly used in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…with no preferred orientation of the nanostructure or for unidirectional orientation of the nanostructure parallel to the rotation axis (Schroer et al, 2006;Feldkamp et al, 2009;Jensen et al, 2011). Skjønsfjell et al (2016) have shown that, with strict assumptions on the sample, the orientation distribution can be retrieved from measurements using a single rotation axis by fitting a model of the X-ray scattering to the experimental SAXS pattern. For more general anisotropically oriented scatterers, SAXS acquisition using two rotation axes is needed (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…with no preferred orientation of the nanostructure or for unidirectional orientation of the nanostructure parallel to the rotation axis (Schroer et al, 2006;Feldkamp et al, 2009;Jensen et al, 2011). Skjønsfjell et al (2016) have shown that, with strict assumptions on the sample, the orientation distribution can be retrieved from measurements using a single rotation axis by fitting a model of the X-ray scattering to the experimental SAXS pattern. For more general anisotropically oriented scatterers, SAXS acquisition using two rotation axes is needed (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments have enabled the tomographic reconstruction of the orientation for anisotropically scattering samples (Skjønsfjell et al, 2016;Schaff et al, 2015;Liebi et al, 2015Liebi et al, , 2018Gao et al, 2019). Under strict assumptions on the sample, such as known dimensions of the scattering particles and slowly varying orientation confined in one plane, the orientation distribution can be obtained from a single rotation axis (Skjønsfjell et al, 2016). For general anisotropically oriented scatterers, two rotation axes are used to retrieve the 3D reciprocal space (Schaff et al, 2015;Liebi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the GISAXS-CT method, CT images are ISSN 1600-5767 reconstructed from sinograms obtained by scanning GISAXS measurements along the direction (Y) perpendicular to the X-ray beam at each rotation angle (). This technique has been applied to transmission smallangle X-ray scattering (SAXS)-CT as well as GISAXS-CT methods (Schroer et al, 2006;Schaff et al, 2015;Skjønsfjell et al, 2016;Liebi et al, 2018). Since CT images are reconstructed from the sinograms of the scattering intensities, one can obtain the spatial distributions of structural information corresponding to the scattering intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Since CT images are reconstructed from the sinograms of the scattering intensities, one can obtain the spatial distributions of structural information corresponding to the scattering intensities. This technique has been applied to transmission smallangle X-ray scattering (SAXS)-CT as well as GISAXS-CT methods (Schroer et al, 2006;Schaff et al, 2015;Skjønsfjell et al, 2016;Liebi et al, 2018). In these methods, CT images are reconstructed from the sinograms using filtered back-projection (FBP).…”
Section: Introductionmentioning
confidence: 99%